Netflix, inc. - media entertainment services - Pontes, Frederico Pamplona Ramos De Oliveira (2020)
In this report, we elaborate an equity valuation of Netflix. The company is facing a very challenging scenario, with new competition threatening its worldwide leading position. Furthermore, this increasing competition is promoting a content war, which is increasing tremendously the cost of streaming content. As a response to this trend, Netflix shifted its strategy to original content production. Through the analysis conducted in this report, Netflix will suffer the impact of the new competition, while being compensated by its international expansion. Our target price is $326.86.